Integrated buried heterostructure DFB laser array for WDM systems based on reconstruction equivalent chirp technique. Issue 6 (June 2015) - Tang, Song; Lu, Jun; Wang, Jeffery; Liu, Yue; Chen, Xiangfei
ABSTRACT: A distributed‐feedback semiconductor laser array with buried heterostructure waveguide based on reconstruction equivalent chirp technique is experimentally demonstrated. The fabricated six‐element laser array has channel spacing of 800 GHz and well meets the International Telecommunication Union standard, with relatively low threshold and high efficiency. Good single‐longitudinal mode operation has been achieved at high injection current (120 mA) and high temperature (80°C), with side mode suppression ratios not lower than 40 dB, which is promising for the future wavelength division multiplexing systems. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1278–1281, 2015